R-Flurbiprofen Improves Axonal Transport in the Tg2576 Mouse Model of Alzheimer’s Disease as Determined by MEMRI - Smith, Karen D.B. (2010)
Axonal pathology is a prevalent feature of Alzheimer’s disease (AD) and is thought to occur predominantly due to the accumulation of amyloid beta (Aβ). However, it remains unclear whether therapeutics geared towards reducing Aβ improves axonal deficits. We have previously used Manganese Enhanced MRI (MEMRI) to demonstrate that axonal transport deficits occur before plaque formation in the Tg2576 mouse model of AD. Here we tested whether axonal transport deficits in the Tg2576 mouse model improve in response to the Aβ42 selective lowering agent R-Flurbiprofen (R-F). We demonstrated that in young animals (before Aβ plaque formation), R-F treatment reduced Aβ42 levels and coincided with a significant improvement in axonal transport (p=0.0186) iHowever, in older animals (after plaque formation had occurred), we observed that R-F treatment did not reduce Aβ42 levels although we still observed a significant improvement in axonal transport as assessed with MEMRI (p=0.0329). We then determined that R-F treatment reduced tau hyper-phosphorylation in the older animals. These data indicate that both Aβ42 and tau comprise a role in axonal transport rate deficits in the Tg2576 models.